IOT and IIOT Security for the South African Maritime and Freight Transport Sectors - Pretorius, Barend; van Niekerk, Brett (Scientia Militaria - South African Journal of Military Studies, 2023)
The advent of the Fourth Industrial Revolution (4IR) has seen a rapid increase in connected smart devices known as the Internet of Things (IoT). While this ‘revolution’ is most noticeable in commercial devices, there has also been an evolution in industrial devices, known as the Industrial Internet of Things. As Africa – and in particular South Africa – is racing to compete in the 4IR, various sectors, including the transport sector, are introducing innovative projects. However, the Internet of Things and the Industrial Internet of Things present cybersecurity risks. Cybersecurity itself is also considered a key component of the 4IR; yet, organisations often neglect to consider the security implications of the Internet of Things. The current research aimed to evaluate and prioritise cyber threats, vulnerabilities, and risk related to the Internet of Things and the Industrial Internet of Things in the South African physical transport sector. This article focuses on the responses to a questionnaire to obtain quantitative data from those with experience in the related fields. The threats and vulnerabilities of concern are illustrated, and the risks are evaluated based on the perceived impact of such risks and the likelihood of the Internet of Things and the Industrial Internet of Things being compromised. While no clear leaders of risk were found, the top three risks based on the perceived severity and likelihood are unavailability of Internet of Things and Industrial Internet of Things devices and/or networks, damage to reputation, and cyberespionage.